Make : Volume 73 : DIY heroes - Senese, Mike (Make : Community, 2020)
The Covid-19 crisis has been a defining moment for the maker movement. Groups and individuals are designing and producing personal protective equipment like face shields and masks, forming grassroots organizations to deliver equipment to medical professionals, and engaging with doctors and nurses to improve the designs and materials they're producing. We're calling this civic response from makers all over the world "Plan C," the backup plan for the backup plan. In this issue we highlight the Plan C people and projects that have driven the maker response and saved lives, and show the DIY PPE you can make to help your community too. We also showcase projects and tips to get you through shelter-in-place orders, like building a 20-second musical hand soap dispenser, transitioning to homeschooling, and delving into webcasting tech. And there are a few kid-friendly projects to help you parents keep your sanity. Plus, over 39 projects including: Build a mini jacob's ladder Make a fully functional cell phone with a rotary dial Construct a simple boomerang that flies indoors and out Tell time with a unique "rewrite" clock using sequins and much more!